Bilateral Facial Diplegia: A Rare Presenting Symptom of Lyme. (16th March 2017) - Ashurst, John; Perry, Matthew
Abstract : Lyme disease is a common disease that is faced by the physician but also acts a mimicker of many other disease processes. Facial palsies, especially bilateral, are a relatively rare presenting symptom of Lyme disease and may warrant further investigation. A thorough history and physical examination coupled with precision testing may aid the physician when faced with a patient with the diagnostic dilemma of facial diplegia.